Genome Plasticity and Polymorphisms in Critical Genes Correlate with Increased Virulence of Dutch Outbreak-Related Coxiella burnetii Strains - Kuley, Runa; Kuijt, Eric; Smits, Mari A.; Roest, Hendrik I. J.; Smith, Hilde E.; Bossers, Alex (Frontiers in Microbiology, 2017)
Coxiella burnetii is an obligate intracellular bacterium and the etiological agent of Q fever. During 2007-2010 the largest Q fever outbreak ever reported occurred in The Netherlands. It is anticipated that strains from this outbreak demonstrated an increased zoonotic potential as more than 40,000 individuals were assumed to be infected. The acquisition of novel genetic factors by these C. burnetii outbreak strains, such as virulence-related genes, has frequently been proposed and discussed, but is not proved yet. In the present study, the whole genome sequence of several Dutch strains (CbNL01 and CbNL12 genotypes), a few additionally selected strains from different geographical locations and publicly available genome sequences were used for a comparative bioinformatics approach. The study focusses on the identification of specific genetic differences in the outbreak related CbNL01 strains compared to other C. burnetii strains. In this approach we investigated the phylogenetic relationship and genomic aspects of virulence and host-specificity. Phylogenetic clustering of whole genome sequences showed a genotype-specific clustering that correlated with the clustering observed using Multiple Locus Variable-number Tandem Repeat Analysis (MLVA). Ortholog analysis on predicted genes and single nucleotide polymorphism (SNP) analysis of complete genome sequences demonstrated the presence of genotype-specific gene contents and SNP variations in C. burnetii strains. It also demonstrated that the currently used MLVA genotyping methods are highly discriminatory for the investigated outbreak strains. In the fully reconstructed genome sequence of the Dutch outbreak NL3262 strain of the CbNL01 genotype, a relatively large number of transposon-linked genes were identified as compared to the other published complete genome sequences of C. burnetii. Additionally, large numbers of SNPs in its membrane proteins and predicted virulence-associated genes were identified in all Dutch outbreak strains compared to the NM reference strain and other strains of the CbNL12 genotype. The presence of large numbers of transposable elements and mutated genes, thereof most likely resulted in high level of genome rearrangements and genotype-specific pathogenicity of outbreak strains. Thus, the epidemic potential of Dutch outbreak strains could be linked to increased genome plasticity and mutations in critical genes involved in virulence and the evasion of the host immune system.